What Drives Generation Z to Purchase Kahf Skincare? The Role of Islamic Branding, Electronic Word-of-Mouth, and Product Quality - Fery Firdaus; Yan Putra Timur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to examine the effect of Islamic branding, e-WOM, and product quality on the purchase intention of Kahf skincare among Generation Z in East Java. This research uses a quantitative approach with an associative research design. Data were collected through questionnaires distributed to male Generation Z aged 13–28 years who live in East Java and are familiar with Kahf skincare products. The sampling technique used was purposive sampling with a total of 100 respondents. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that Islamic branding does not have a significant effect on the purchase intention of Kahf skincare, whereas e-WOM and product quality have a significant effect. These findings show that, in the context of male Generation Z consumers in East Java, purchase intention is driven more strongly by digital consumer information and perceived product quality than by Islamic branding, which tends to function as a baseline trust element rather than a primary purchase driver.